Systems, Boundaries, and Information Flow - Brown, Warren B. (Academy of Management Journal, 1966)
In the attempts to make the study of administration more scientific, one promising technique is the systems analysis approach.1 This has its roots deeply planted in the physical and biological sciences and hence carries with it an aura of respectability. However, its usefulness for the study of human organizations is not yet established, though we certainly can remain optimistic at this point. This paper uses a general systems framework to explore some selected aspects of organizational boundary problems, especially those concerning information flows.